2011
DOI: 10.1101/lm.024042.111
|View full text |Cite
|
Sign up to set email alerts
|

Myosin II motor activity in the lateral amygdala is required for fear memory consolidation

Abstract: Learning induces dynamic changes to the actin cytoskeleton that are required to support memory formation. However, the molecular mechanisms that mediate filamentous actin (F-actin) dynamics during learning and memory are poorly understood. Myosin II motors are highly expressed in actin-rich growth structures including dendritic spines, and we have recently shown that these molecular machines mobilize F-actin in response to synaptic stimulation and learning in the hippocampus. In this study, we report that Myos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 36 publications
4
44
0
Order By: Relevance
“…We and others have previously demonstrated that learning triggers a brief window of F-actin dynamics, such that depolymerization at the time of training prevents the consolidation of hippocampus- and amygdala-dependent fear memories (30, 34-37). However, this window of actin cycling closes quickly (30, 37), stabilizing the long-term memory. As a result, intra-BLC blockade of F-actin cycling prior to testing fails to disrupt the expression of an auditory fear memory or a food reward place preference (Fig.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…We and others have previously demonstrated that learning triggers a brief window of F-actin dynamics, such that depolymerization at the time of training prevents the consolidation of hippocampus- and amygdala-dependent fear memories (30, 34-37). However, this window of actin cycling closes quickly (30, 37), stabilizing the long-term memory. As a result, intra-BLC blockade of F-actin cycling prior to testing fails to disrupt the expression of an auditory fear memory or a food reward place preference (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Unlike the impact of actin depolymerization on a METH-associated contextual memory, another BLC-dependent memory, auditory fear (35, 61), is known to become insensitive to blockade of polymerization within minutes of learning (30, 37), such that pre-test BLC blockade has no effect on the memory (34, 37). To further investigate the specificity of this effect on METH-associated memory, we explored the possibility that appetitive memories, in general, are susceptible to actin depolymerization days after training (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial studies using blebbistatin demonstrated that the position of the cytokinetic cleavage furrow is maintained by signals from microtubules controlling nonmuscle myosin II localization [26]. Targeted inhibition of myosin II with blebbistatin has also revealed that nonmuscle myosin II plays a role in fear memory consolidation in the lateral amygdala [62], that nonmuscle myosin IIA and IIB regulate the migration of rat hepatic stellate cells [63] and that nonmuscle myosin II is required for the ligand-induced internalization of the EGFR [64]. In addition, depletion of myosin ATPase activity in plant cells using BDM demonstrates that chloroplast actin filaments reorganize in a manner independent of chloroplast movement [65] and that the actomyosin complex mediates early transduction events during the gravitropic response of snapdragon spikes [66].…”
Section: Scientific Insight From Inhibitor Usementioning
confidence: 99%